Full-mouth rehabilitation with fixed restoration - Adriani Dachri; Edy Machmud (Indonesia Prosthodontic Association, 2023)
A 32-year-old male patient with chief complaint of difficulty chewing food due to tooth loss was referred to Hasanud-din University Dental Hospital. Intraoral examination showed edentulous teeth 15, 16, 26, 36, 37, 46 and 47. Radio-graph showed no radiolucency and crown root ratio of 1:2. The treatment was full mouth rehabilitation using an adhe-hesive bridge and a fixed bridge on the upper jaw, and a telescopic crown overdenture on the lower jaw. Initial im-pressions were taken for diagnostic modeling and temporary denture fabrication. Preparations were performed in a box shape on occlusal teeth 25 and 27 for the fabrication of a fixed bridge and preparation of teeth 14 and 17 for the fabrication of a fixed bridge, followed by the double impression method and bite registration. Insertion of adhe-sive bridges and fixed bridgework followed by preparation of 35, 38, 45 and 48 for primary denture fabrication on telescopic crowns. Secondary impressions were made using elastomeric materials. Primary crowns of teeth 35, 38, 45 and 48 were made first and cementation followed by mandibular secondary impressions. Bite registration was taken and the maxillomandibular relationship was recorded. Afterwards, metal frame try-in, posterior tooth try-in, laboratory processing and then insertion were performed. It was concluded that prosthetic rehabilitation is essen-tial, an adequate treatment plan should be put in place to improve the patient's mastication and maintain the stoma-matognathic system with denture fabrication.